Assessment of the changes in seed yield and nutritional quality of quinoa grown under rainfed Mediterranean environments - Matías, Javier; Rodríguez, María José; Cruz, Verónica; Calvo, Patricia; Granado-Rodríguez, Sara; Poza-Viejo, Laura; Fernández-García, Nieves; Olmos, Enrique; Reguera, María (Frontiers in Plant Science, 2023)
Climate change is considered a serious threat to agriculture and food security. It is linked to rising temperatures and water shortages, conditions that are expected to worsen in the coming decades. Consequently, the introduction of more drought-tolerant crops is required. Quinoa (Chenopodium quinoa Willd.) has received great attention worldwide due to the nutritional properties of its seeds and its tolerance to abiotic stress. In this work, the agronomic performance and seed nutritional quality of three quinoa varieties were studied during two consecutive years (2019-2020) under three water environmental conditions of Southwestern Europe (irrigated conditions, fresh rainfed, and hard rainfed) with the goal of determining the impact of rainfed conditions on this crop performance. High precipitations were recorded during the 2020 growing season resulting in similar grain yield under irrigation and fresh rainfed conditions. However, in 2019, significant yield differences with penalties found under water-limiting conditions were found among the evaluated environmental conditions. Furthermore, nutritional and metabolomic differences were observed among seeds harvested from different water environments including the progressive accumulation of glycine betaine accompanied by an increase in saponin and a decrease in iron with water limitation. Also, water-limiting environments were associated with increased protein contents. Overall, this work contributes to gaining further knowledge about how water availability affects quinoa field performance, as it might impact both seed yield and quality. It also can help reevaluate rainfed agriculture, as water deficit can positively impact the nutritional quality of seeds.